Bioinspired multifunctional layered magnetic hybrid materials - Debus, Christian; Wu, Baohu; Kollmann, Tina; Duchstein, Patrick; Siglreitmeier, Maria; Herrera, Steven; Benke, Dominik; Kisailus, David; Schwahn, Dietmar; Pipich, Vitally; Faivre, Damien; Zahn, Dirk; et al. (Bioinspired, Biomimetic and Nanobiomaterials, 2019)
Nature has taken millennia to come up with unique solutions for providing materials with properties tailored toward versatile demands, making use of the very limited resources available in natural environments. Today, these biomaterials can be used as inspiration by combining and 'remixing' the concepts that nature displays to create new bioinspired materials. Here, the authors present materials combining the structural and functional elements of multiple biominerals: the inorganic-organic lamellar structure responsible for the high fracture toughness of nacre; highly mineralized composites, which give different mollusk teeth their very high hardness and strength; and the particle orientation and magnetic anisotropy of magnetosomes, giving magnetotactic bacteria a sensitive means to navigate along geomagnetic field lines. The authors show how the mechanical properties of a composite material can be improved with the addition of each of these elements. Small-angle neutron scattering studies and molecular simulation give additional insights into the mineralization from the very first attached ions to the finished composite.
CRIS-Team WoS Importer:2019-04-02

Multifunctional layered magnetic composites - Siglreitmeier, Maria; Wu, Baohu; Kollmann, Tina; Neubauer, Martin; Nagy, Gergely; Schwahn, Dietmar; Pipich, Vitaliy; Faivre, Damien; Zahn, Dirk; Fery, Andreas; Coelfen, Helmut (Beilstein Journal of Nanotechnology, 2015)
A fabrication method of a multifunctional hybrid material is achieved by using the insoluble organic nacre matrix of the Haliotis laevigata shell infiltrated with gelatin as a confined reaction environment. Inside this organic scaffold magnetite nanoparticles (MNPs) are synthesized. The amount of MNPs can be controlled through the synthesis protocol therefore mineral loadings starting from 15 wt % up to 65 wt % can be realized. The demineralized organic nacre matrix is characterized by small-angle and verysmall- angle neutron scattering (SANS and VSANS) showing an unchanged organic matrix structure after demineralization compared to the original mineralized nacre reference. Light microscopy and confocal laser scanning microscopy studies of stained samples show the presence of insoluble proteins at the chitin surface but not between the chitin layers. Successful and homogeneous gelatin infiltration in between the chitin layers can be shown. The hybrid material is characterized by TEM and shows a layered structure filled with MNPs with a size of around 10 nm. Magnetic analysis of the material demonstrates superparamagnetic behavior as characteristic for the particle size. Simulation studies show the potential of collagen and chitin to act as nucleators, where there is a slight preference of chitin over collagen as a nucleator for magnetite. Colloidal-probe AFM measurements demonstrate that introduction of a ferrogel into the chitin matrix leads to a certain increase in the stiffness of the composite material.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bio-inspired mineralization; Biomineralization; Chitin; Ferrogel; Hybrid materials; Magnetite; Nacre

Synthesis and Characterization of Gelatin-Based Magnetic Hydrogels - Helminger, Maria; Wu, Baohu; Kollmann, Tina; Benke, Dominik; Schwahn, Dietmar; Pipich, Vitaliy; Faivre, Damien; Zahn, Dirk; Coelfen, Helmut (Advanced Functional Materials, 2014)
A simple preparation of thermoreversible gelatin-based ferrogels in water provides a constant structure defined by the crosslinking degree for gelatin contents between 6 and 18 wt%. The possibility of varying magnetite nanoparticle concentration between 20 and 70 wt% is also reported. Simulation studies hint at the suitability of collagen to bind iron and hydroxide ions, suggesting that collagen acts as a nucleation seed to iron hydroxide aggregation, and thus the intergrowth of collagen and magnetite nanoparticles already at the precursor stage. The detailed structure of the individual ferrogel components is characterized by small-angle neutron scattering (SANS) using contrast matching. The magnetite structure characterization is supplemented by small-angle X-ray scattering and microscopy only visualizing magnetite. SANS shows an unchanged gelatin structure of average mesh size larger than the nanoparticles with respect to gel concentration while the magnetite nanoparticles size of around 10 nm seems to be limited by the gel mesh size. Swelling measurements underline that magnetite acts as additional crosslinker and therefore varying the magnetic and mechanical properties of the ferrogels. Overall, the simple and variable synthesis protocol, the cheap and easy accessibility of the components as well as the biocompatibility of the gelatin-based materials suggest them for a number of applications including actuators.
EAM Import::2019-03-12